Search for two-photon production of resonances decaying into K Mathematical expression and K Mathematical expressionπ - Althoff, M; Braunschweig, W; Kirschfink, F; Martyn, H; Rosskamp, R; Siebke, H; Wallraff, W; Eisenmann, J; Fischer, H; Hartmann, H; Jocksch, A; Knop, G; et al. (Springer-Verlag, 1985)
An analysis of the production of KS0KS0 and K±Ks0π∓ by two quasi-real photons is presented. The cross section for γγ→K0 Mathematical expression, which is given for the γγ invariant mass range from K Mathematical expression threshold to 2.5 GeV, is dominated by the f′(1525) resonance and an enhancement near the K Mathematical expression threshold. Upper limits on the product of the two-photon width times the branching ratio into K Mathematical expression pairs are given for Θ(1700), h(2030), and ξ(2220). For exclusive two-photon production of K±Ks0π∓ no significant signal was observed. Upper limits are given on the cross section of γγ→K+ Mathematical expressionπ- or K-K0π+ between 1.4 and 3.2 GeV and on the product of the γγ width times the branching ratio into the K Mathematical expressionπ final states for the ηc(2980) and the ι(1440), yielding Γ(γγ)→i(1440))·BR(i(1440)→K Mathematical expressionπ<2.2 keV at 95% C.L. © 1985 Springer-Verlag.